Transnational students' attachment to place in campus: towards the internationalization of Universiti Putra Malaysia - Mat Raschid, Mohammad Yazah; Fatemi, Ezaz; Sharif, Roslina; Ismail, Abdul Halim (Jabatan Seni Bina, Fakulti Kejuruteraan & Alam Bina, Universiti Kebangsaan Malaysia, 2017)
In many universities around the world internationalization is promoted as a top priority to attract lucrative international student markets. To achieve this goal, it is essential to facilitate a sense of place amongst transnational students to eradicate social and psychological problems in the new educational environment. Despite this, there seems to be insufficient records on the actual manner of transnational students’ securitizing the issue and how it has impacted their educational lifestyles. Therefore, the challenge now is to ascertain the actual level of attachment in campus before embarking into a more related complex and multidisciplinary social and physical studies. The aim of this study to investigate the level of emotional attachment of place of international students and the manner it affects their educational experiences in Universiti Putra Malaysia (UPM) main campus. For this reason, a 5-point Likert-Scaled questionnaire survey on 336 UPM international students and data analysis using SPSS were conducted. Results demonstrate that the international students have a low emotional place attachment towards the campus design which also affects their social well-being and psychological health. Recognizing the main indicators of emotional attachment also assist in improving the physical design of the campus to support the international students’ sense of place attachment.